Maintenance of embryogenic potential of calli derived from embryonic shoot of West Coast Tall cv. of coconut (Cocos nucifera L.) - Bhavyashree, U.; Jayaraj, K. Lakshmi; Rachana, K.E.; Muralikrishna, K.S.; Sajini, K.K.; Rajesh, M.K.; Karun, Anitha (Journal of Plantation Crops, 2015)
Maintenance of embryogenic potential of calli is important as the totipotency is often lost in a short time in vitro. This caters to the need for year round availability of somatic embryos in a regenerable state. In the present study, 14 media combinations, with either 2,4-D or picloram as auxin source, were tested for maintaining embryogenic calli obtained from embryonic shoot explants of coconut. Irrespective of type and concentration of auxins, callusing was observed in all the media combinations. However, high dose of 2,4-D (above 74.6 μM) in the initial medium resulted in intense browning and lesser percentage of callusing. Embryogenic nature of calli could be maintained to a maximum of 21 weeks in medium supplemented with 2,4-D (74.6 μM) and subsequent culturing into higher concentration of 2,4-D (90.4 μM). Gene expression studies carried out using qRT-PCR revealed that genes such as ECP, GST, LEAFY and WUS were highly expressed in long term embryogenic calli (21 week old) and genes such as SERK, GLP, WRKY and PKL in initial embryogenic calli (21 days old). The study concludes that coconut plumular calli could be maintained for longer periods without compromising on the embryogenic potential of the calli.